O imaginário cristõa seiscentista: uma análise histórico-simbólica da obra O Peregrino de John Bunyan - Oliveira Neto, Estevão Domingos de (2011)
The purpose of this research is to investigate the symbolic-mythological imaginary of seventeenth century Puritan Protestantism, based on the work of John Bunyan, The Pilgrim. The study was developed within the Graduate Program in Sciences of Religions at the Federal University of Paraíba (UFPB), in the research line Religion, Culture and Symbolic Production, by Research and Study Group in Anthropology and the Imaginary (GEPAI). The objective is to identify the mythical and imaginary roots of the Christian imaginary which are present in such work. The historical context in which such work was produced with all religious, philosophical and political conflicts are described. The approach offers elements to realize the mythic-ideological dimension present in John Bunyan s speech. He was a preacher of the Gospel (pastor), forged in an atmosphere of great tension, representative of Protestantism dissent known as Puritan . He used the resource of allegory as a support for the metaphors. The work narrates the trajectory of a Christian towards the Heavenly City. The symbolic-mythological element is present in all the work. This paper aims to bring near the allegory present in the work to the Christian Protestant imaginary. The work was originally published in 1678. The author was in prison for twelve years, and it was during this time that he wrote this, which is his masterpiece. The plot of this novel mingles to the symbolic interpretation. The theoretical analysis adopted is the Theory of the Imaginary by Gilbert Durand. The cultural imaginary consists of a dynamic system, organizer of images, mixture of mythical fragments generated by the human imagination and does not constitute of a secondary element of man s thinking, but in the very matrix of this thought. As a second Theoretical reference is Joseph Campbell, with his work about The Hero Adventure. The proposal is to identify the pilgrim journey in the work of Bunyan with the thesis of the conception of the mythological hero in Campbell. The myths are manifested in the symbolic acts, whose function is to put the man in a relationship of meaning with the world, with the other self and with his own self. There is a logic in all the imaginary mythological building process, in such a way that its phenomenology can be investigated and explained. Methodologically, the research consists in a descriptive and bibliographical study, associated with the studies of the imaginary according to Durand, and the hero adventure according to Campbell. The experience described by Bunyan illustrates our own experience. To tell the truth, all of us are pilgrims in this world, all of us walk in the direction of what is there and beyond, in one way or another, may it be in the plurality of how we feel, perceive and believe, may it be in the singularity of our inner beliefs.